Capital in the 21st Century: Are the Thomas Piketty’s Ideas a Way to Welfare and Prosperity or Enslavement? - Hoppe, Grzegorz (Journal of Corporate Responsibility and Leadership, 2018)
In his seminal work Capital in the 21st century Thomas Piketty analyses income and wealth disparities in developed econ-omies observed over last two centuries. He claims that increasing disparities may result in social tensions and even revolutions in the near future and proposes fiscal mechanisms as a remedy to such threats. The aim of the paper is to assess the Piketty’s proposals of tax changes aimed at levelling the existing income disparities. First of all, the paper proves that Piketty’s tax proposals are contrary to the empirically tested Laffer curve. Secondly, it discusses whether social stratification is or should be a worry for economists and politicians or whether it is a required and unavoidable situation in a well developing market economy.